THE EFFECT OF VIDEO MEDIA PROVIDING INFORMATION ABOUT BLOOD ENHANCER TABLETS ON KNOWLEDGE IN FEMALE ADOLESCENTS - Wahidah, Fitri Nur; Wijayanti, Wijayanti (Journal of Advanced Nursing and Health Sciences, 2025)
Background: Based on the result of basic health research Riskesdas in 2018, as many as 23,7% of women aged 14-25 years nationally suffer from anaemia. About three to four out of ten adolescent girls, or about 32% of adolescent girls have anaemia. This study aims to determine the effect of providing video content about iron tablets on the understanding of adolescent girls at SMP N 1 Sragi.Methods: This research is quantitative with a quasi-experimental design consisting of two groups, namely experimental and control. The experimental group was given an educational video about blood enhancer tablets, while the control group was given a lecture. The research instrument used a questionnaire. The age of the respondents was 13 to 15 years old. The research sample consisted of 67 students. The T-test is used to test data.Results: The average score in the experimental group was 8.76, while in the control group it was 6,45. There was an increase of 2.31, with a p-value of <0.005, which means that there is a significant influence on average before and after treatment.Conclusion: To reduce the prevalence of anaemia, especially in adolescent girls, it is expected that this study will improve the understanding of teenage girls, especially about blood tablets.